2003
DOI: 10.1136/jramc-149-01-08
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality And Soldiery Combat & Condoms, Continence & Cornflakes

Abstract: The results of a short sexual health study of 75 male soldiers undertaking humanitarian aid relief in Africa are presented in an historical context relating to sexuality and soldiery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Anastario et al (2013) argued in their conceptual paper that deployment leads to less sexual behavioural risk. This is supported by an early study by Palmer (2003) reporting that deployment acted as a mechanism to diminish the libido. Hyams et al (1995) found that infectious diseases were not a major cause of lost manpower during the two Iraq wars.…”
Section: Deploymentsupporting
confidence: 63%
See 4 more Smart Citations
“…Anastario et al (2013) argued in their conceptual paper that deployment leads to less sexual behavioural risk. This is supported by an early study by Palmer (2003) reporting that deployment acted as a mechanism to diminish the libido. Hyams et al (1995) found that infectious diseases were not a major cause of lost manpower during the two Iraq wars.…”
Section: Deploymentsupporting
confidence: 63%
“…Self-administered surveys have been used with success in sexual health research in many military organisations (Todd et al 2012;Baud 2008;Shafer et al 2008;Greene et al 2007;Palmer 2003;Fioravante et al 2005;Skaza et al 2003;Crutcher & Papdimos 1992). Lessons to enhance success drawn from previous research include the maintenance of confidentiality (Todd et al 2012;Baud 2008;Fioravante et al 2005); use of language familiar to the participants (Greene et al 2007); dedicated time to complete the survey (Anastario 2013;Shafer et al 2008;Skaza et al 2003); and awareness by the participant of the purpose and value of the study (Baud 2008;Shafer et al 2008;Skaza et al 2003;Crutcher & Papdimos 1992).…”
Section: Survey Toolmentioning
confidence: 99%
See 3 more Smart Citations